1995
DOI: 10.1128/jcm.33.10.2525-2529.1995
|View full text |Cite
|
Sign up to set email alerts
|

Controlled clinical comparison of Isolator and BACTEC 9240 Aerobic/F resin bottle for detection of bloodstream infections

Abstract: A controlled clinical comparison was carried out with the BACTEC 9240 Aerobic/F resin bottle and the Isolator system with adult patients suspected of having bloodstream infections. A total of 10,500 paired specimens were collected, of which 1,122 from 520 patients were positive. There were 68 false-positive BACTEC bottles; 259 positive cultures that were excluded from analysis because the bottle, the Isolator, or both failed to meet the minimum volume criterion of 8 ml of blood; and 207 positive cultures that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…In the current study, we compared two aerobic blood culture systems simultaneously. The results of our study are generally in agreement with those from another study, by Pohlman and colleagues (7), which also compared the performance of the Isolator aerobic culture system to the BACTEC Plus Aerobic/F resin bottle. Like our study, Pohlman and colleagues showed that statistically significantly more isolates of S. aureus and coagulase-negative Staphylococcus spp.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we compared two aerobic blood culture systems simultaneously. The results of our study are generally in agreement with those from another study, by Pohlman and colleagues (7), which also compared the performance of the Isolator aerobic culture system to the BACTEC Plus Aerobic/F resin bottle. Like our study, Pohlman and colleagues showed that statistically significantly more isolates of S. aureus and coagulase-negative Staphylococcus spp.…”
Section: Discussionsupporting
confidence: 92%
“…Conventional blood culture seems to be insensitive compared with the newly developed blood tests (Makimura et al , 1994; Obayashi et al , 1995). During the past two decades, there have been a number of changes in blood culture practices and systems (Auckenthaler et al , 1982; Plorde et al , 1985; Murray et al , 1991; Weinstein et al , 1991; Gutierrez et al , 1995; Pohlman et al , 1995a,b; Weinstein, 1996). However, the sensitivity of blood cultures has decreased since 1990.…”
Section: Discussionmentioning
confidence: 99%
“…During the past two decades, there have been a number of changes in blood culture practices (Auckenthaler et al , 1982; Plorde et al , 1985; Weinstein, 1996). Manufacturers of blood culture systems and media have improved their products (Murray et al , 1991; Weinstein et al , 1991; Pohlman et al , 1995a,b), and there has been a marked trend towards the use of automated systems – most recently, continuous‐monitoring blood culture devices (Gutierrez et al , 1995).…”
mentioning
confidence: 99%
“…62,63 Although routine blood culture systems have been shown to be highly sensitive for detection of candidemia and cryptococcemia, automated blood culture systems are insensitive for cultivation of monomorphic and dimorphic molds. Isolation of molds (and fastidious bacteria) from blood requires the lysiscentrifugation method (Isolator) [64][65][66] or the use of enriched fungal medium bottles. 67,68 S. pneumoniae can be recovered from urine cultures in as many as 38% of patients with pneumococcal pneumonia.…”
Section: Cap and Hap/vap Virusesmentioning
confidence: 99%